Normality of the p-Harmonic and Log-p-Harmonic Mappings. (6th November 2020) - Jiang, Qinghua; Meng, Fanning; Dang, Guoqiang
Abstract : In this paper, the concepts of p-harmonic mappings and log-p-harmonic mappings in the unit disk have been introduced and studied by many researchers. We proved the normality of the p-harmonic mappings and log-p-harmonic mappings, which extend the related results of harmonic mappings of earlier authors.